Effect of Coping Skills Training on Quality of Life among Parents of Children with Leukemia - Sedigheh Khanjari; Naiemeh Seyedfatemi; Somayeh Borji; Hamid Haghani (Tehran University of Medical Sciences, 2014)
Background & Aim: Cancer is the most common childhood chronic medical illnesses that can affect quality of life of the children and their families. The aim of this study was to determine the effect of coping skills training on quality of life among parents of children with leukemia.   Methods & Materials: This non-randomized clinical trial was conducted from March to June 2013. Ninety eight parents of children with leukemia who were referred to two selected hospitals affiliated to Tehran University of Medical Sciences were enrolled to study using convenience sampling method. The participants were allocated to two experimental (n=48) and control (n=50) groups. Data were collected through two questionnaires including demographic characteristics of the parents and children, and the Persian version of the Caregivers Quality Of Life index Cancer. Coping skills training including social communication skills was performed through small group discussion (5-8 members) in four 2-hours sessions for the experimental group. The questionnaires were completed four weeks after the intervention by the parents. Data were analyzed using the independent t-test, paired t-test, Fisher's exact test and Chi-squared test in the SPSS-16.   Results: The results showed significant increase in the overall quality of life after the intervention (P<0.001). The quality of life of parents in the experimental group was improved significantly in comparison with the control group (P=0.045). Mental/emotional burden (P<0.001) and lifestyle disruption (P<0.001) decreased significantly after the intervention.   Conclusion: The coping skills training affected the quality of life among parents of children with leukemia . Effective educational interventions may help to increase the quality of life of parents who have children with Leukemia.